2024
DOI: 10.3389/fpsyg.2024.1349002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural nuances in sarcasm comprehension: a comparative study of Chinese and American perspectives

Yiran Du,
Huimin He,
Zihan Chu

Abstract: It is evident that sarcasm can be interpreted differently due to various factors, However, rare research was conducted to investigate the influence of national culture on sarcasm comprehension despite its valuable theoretical implication. This study used an online rating task to explore how national culture impacts the comprehension of sarcasm, focusing on the differences between Chinese and American cultural values (i.e., power distance, uncertainty avoidance, collectivism, long-term orientation, and masculin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This study found that American participants perceive and interpret verbal irony more effectively than their Chinese counterparts. This finding is consistent with previous research by Du et al (2024) and partially aligns with the research conducted by Zhu and Filik (2023), which demonstrated that UK participants, representing western cultures, tend to use sarcasm more frequently than Chinese participants, who represent eastern cultures. This may be due to less use of verbal irony in eastern cultures (Blasko et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study found that American participants perceive and interpret verbal irony more effectively than their Chinese counterparts. This finding is consistent with previous research by Du et al (2024) and partially aligns with the research conducted by Zhu and Filik (2023), which demonstrated that UK participants, representing western cultures, tend to use sarcasm more frequently than Chinese participants, who represent eastern cultures. This may be due to less use of verbal irony in eastern cultures (Blasko et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…This group was also aged between 18 and 24 years, (M = 21.62, SD = 1.79). The sample size of the study was based on previous study using similar stimuli (Du et al, 2024;Garcia et al, 2022).…”
Section: Methods 21 Participantsmentioning
confidence: 99%
See 3 more Smart Citations